2016
DOI: 10.1038/bjc.2016.200
|View full text |Cite
|
Sign up to set email alerts
|

FAM19A4 methylation analysis in self-samples compared with cervical scrapes for detecting cervical (pre)cancer in HPV-positive women

Abstract: Background:High-risk human papillomavirus (hrHPV)-positive women require triage to identify those with cervical high-grade intraepithelial neoplasia and cancer (⩾CIN3 (cervical intraepithelial neoplasia grade 3)). FAM19A4 methylation analysis, which detects advanced CIN and cancer, is applicable to different sample types. However, studies comparing the performance of FAM19A4 methylation analysis in hrHPV-positive self-samples and paired physician-taken scrapes are lacking.Methods:We compared the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 42 publications
7
75
2
Order By: Relevance
“…Cervical cancer development after a persistent infection with high‐risk HPV is driven by additional host cell changes such as altered DNA methylation 12, 17, 20, 21. In earlier work, we have shown that methylation assays targeting FAM19A4 and/or mir124‐2 genes have competitive performance against other triage options 22, 23, 24, 25, 26. In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cervical cancer development after a persistent infection with high‐risk HPV is driven by additional host cell changes such as altered DNA methylation 12, 17, 20, 21. In earlier work, we have shown that methylation assays targeting FAM19A4 and/or mir124‐2 genes have competitive performance against other triage options 22, 23, 24, 25, 26. In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24.…”
Section: Introductionmentioning
confidence: 97%
“…In cross‐sectional and short‐term clinical follow‐up studies among both cervical screening and gynecologic outpatient populations, FAM19A4 methylation analysis has shown a similar sensitivity for cervical intraepithelial neoplasia lesions or worse (CIN3+) as compared to cytology 22, 24. Methylation levels of these genes in cervical scrapes increase with the severity of underlying cervical lesion 22, 25. Of interest, FAM19A4 methylation analysis detects (virtually) all cervical carcinomas, and has proven to be more sensitive than cytology for the detection of CIN3 lesions with a longer duration of existence 27.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, host cell methylation analysis of CADM1, MAL, mir124-2, and FAM19A4 in cervical scrapes allows the discrimination of high-grade CIN with a long-term preceding hrHPV-infection from those with a short-term hrHPV infection [95,96]. Concordantly, in both cervical scrapes and selfsampled cervicovaginal lavages, methylation levels of FAM19A4 have been shown to correspond with the estimated CIN lesion volume [100]. Methylation levels of CADM1, MAL, mir124-2, and FAM19A4 are extraordinarily high in cervical scrapes of women with carcinomas [96,101], resulting in a 100% sensitivity for carcinomas of methylation assays targeting these genes, even when very high thresholds are used to define methylation positivity.…”
mentioning
confidence: 85%
“…The combination of Pap cytology and methylation analysis, which have been suggested to serve as complementary markers in terms of detection of early and advanced CIN [32], could serve as a sensitive strategy that, in contrast to Pap cytology alone, detects all carcinomas and virtually all CIN3. Table 5 provides an overview of test characteristics (that is, sensitivity, specificity, NPV, PPV) of Pap cytology, HPV16/18 genotyping, p16/Ki-67 dual-stained cytology, and methylation analysis in a single (outpatient) study population [51,67,100,114]. A general limitation of microscopy-based strategies is the fact that these can only be adequately performed on cervical scrapes collected by health-care professionals.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Methylation testing may be an effective triage tool to detect and characterise women at high risk of developing CIN3. The effectiveness of such tests in predicting CIN3 may influence the screening process in many ways, for example by providing an objective method to reach more accurate prognoses or by helping to avoid overtreatment of women with non-progressive lesions [28-31]. …”
Section: Response(s) To Research Questionnairementioning
confidence: 99%